2007
DOI: 10.1055/s-2007-970143
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Impairment in Psychiatric Inpatients: Focus on Depression

Abstract: Judging from this data, sexual impairment appears to be a frequent and underestimated problem in psychiatric inpatients with a high prevalence across all diagnostic groups, particularly in depressed subjects. Female patients attribute this impairment mainly to their mental illness, whereas male patients tend to assign their impairments primarily to their medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 26 publications
4
29
0
4
Order By: Relevance
“…In their study of incontinent women <30 years old, 16% considered UI extremely embarrassing or humiliating, 6% report feelings of frustration and/or depression, and up to 9% were using antidepressants and/or avoiding venturing outside their home. Interestingly, these depressive factors have also been implicated in women with sexual dysfunction [50].…”
Section: Resultsmentioning
confidence: 99%
“…In their study of incontinent women <30 years old, 16% considered UI extremely embarrassing or humiliating, 6% report feelings of frustration and/or depression, and up to 9% were using antidepressants and/or avoiding venturing outside their home. Interestingly, these depressive factors have also been implicated in women with sexual dysfunction [50].…”
Section: Resultsmentioning
confidence: 99%
“…Again, a double-blind crossover trial found that amitriptyline-fluoxetine combination improved pain scores and total FIQ scores more than either drug alone and more than placebo [28]. Our group added pregabalin to fibromyalgia patients already improved by quetiapine and found that pain and tiredness after awakening subscales of the FIQ, as well as the physical component of the SF-12, additionally improved with quetiapine plus pregabalin combination [29]; the results of this study were similar to those obtained with the combination of pregabalin and trazodone in the present study. Recently, an experimental study has shown, in an animal model of fibromyalgia, a potent antihyperalgesic effect of tramadol combined with milnacipran [30].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 79 randomized, controlled and double-blind trials conducted between 1989 and 2005 with the following antidepressants were identifi ed and included in our analysis: duloxetine (4), milnacipran (10), mirtazapine (19), nefazodone (11), reboxetine (7) and venlafaxine (28). The methods sections of the reviewed research papers were searched for the methodology of adverse event assessment.…”
Section: Methodsmentioning
confidence: 99%